Highlights of the EORTC St. Gallen International Expert Consensus on the primary therapy of gastric, gastroesophageal and oesophageal cancer: differential treatment strategies for subtypes of early gastroesophageal cancer - Lutz, Manfred Paul; Sterzing, Florian (European journal of cancer, 2012)
The 1st St. Gallen EORTC Gastrointestinal Cancer Conference 2012 Expert Panel clearly differentiated treatment and staging recommendations for the various gastroesophageal cancers. For locally advanced gastric cancer (⩾T3N+), the preferred treatment modality was pre- and postoperative chemotherapy. The majority of panel members would also treat T2N+ or even T2N0 tumours with a similar approach mainly because pretherapeutic staging was considered highly unreliable. It was agreed that adenocarcinoma of the gastroesophageal junction (AEG) is classified best according to Siewert et al. Preoperative radiochemotherapy (RCT) is the preferred treatment for AEG type I and II tumours. For AEG type III, i.e. tumours which may be considered as gastric cancer, perioperative chemotherapy is the majority approach. For resectable squamous cell cancer of the oesophagus a clear majority recommended radiochemotherapy followed by surgery as optimal approach, irrespective of tumour size. In contrast, definitive RCT was judged appropriate for advanced tumours with extended lymph node involvement (N2) or for cancers of the upper oesophagus. Additional recommendations are presented on the use of endosonography, PET-CT scan and laparoscopy for staging and on the preferred approach to surgery.